2009
DOI: 10.20885/jsb.vol13.iss1.art6
|View full text |Cite
|
Sign up to set email alerts
|

Pengukuran Indeks Daya Saing Industri Kecil Menengah (IKM) di Jawa Tengah

Abstract: This research aims to analyze the small and medium industries competitiveness in the manufacturing sector in Central Java by using the framework of Porter's diamond model. Measurement of the competitiveness index is using the value established in the industry rankings, the company, dimensions and elements. Based on the results of the index values calculated, small and medium industries in the manufacturing sector in Central Java are highly competitive both for each dimension and overall dimensions. According t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 2 publications
0
4
0
9
Order By: Relevance
“…Peranan UMK dalam perekonomian tidak terlepas dari tantangan yang harus dihadapi, terlebih lagi pada era global sekarang ini. Hal tersebut sesuai dengan pendapat Wiyadi (2009) yang menyatakan bahwa globalisasi menghilangkan batas ekonomi negara di dunia, sehingga muncul tantangan dari dalam maupun luar negeri yang harus dihadapi dalam dunia bisnis. Persaingan bisnis dari meluasnya pasar tidak dapat ditolak tetapi harus dihadapi dengan cara memperkuat bisnis, menciptakan bisnis yang berdaya saing.…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…Peranan UMK dalam perekonomian tidak terlepas dari tantangan yang harus dihadapi, terlebih lagi pada era global sekarang ini. Hal tersebut sesuai dengan pendapat Wiyadi (2009) yang menyatakan bahwa globalisasi menghilangkan batas ekonomi negara di dunia, sehingga muncul tantangan dari dalam maupun luar negeri yang harus dihadapi dalam dunia bisnis. Persaingan bisnis dari meluasnya pasar tidak dapat ditolak tetapi harus dihadapi dengan cara memperkuat bisnis, menciptakan bisnis yang berdaya saing.…”
Section: Pendahuluanunclassified
“…Sumber: (Porter, 1990:78) terlepas dari kritik, (Eickelpasch et al, 2011) (Wiyadi, 2009) menggunakan unsur-unsur sebagai berikut: (a) sumber bahan baku, (b) sumber tenaga kerja, (c) sumber modal, (d) teknologi, (e) lokasi, (f pengetahuan, (g) biaya produk. Pada penelitian ini, mengadopsi unsur-unsur tersebut dengan merubah sumber tenaga kerja menjadi sumber daya manusia karena ruang lingkup sumber tenaga kerja dirasa lebih sempit dan penelitian ini ingin mengetahui kondisi sumber daya manusia pelaku usaha dengan adanya pelatihan atau seminar yang diikutinya, selanjutnya menghilangkan unsur lokasi, karena sekarang sudah ada penjualan sistem online, pengetahuan, sudah termasuk dalam kondisi sumber daya manusia dan biaya produk dapat terlihat dari pengadaan bahan baku.…”
Section: Gambar 1 Porter Diamond Modelunclassified
See 1 more Smart Citation
“…However, if we look at the human resources in all the regions above, it shows that Solok City has a better weight than that of Kota Pariaman, so to improve the competitiveness of Kota Pariaman it is necessary to have a program to increase their knowledge through higher formal education or to take various courses and the training. Increased competitiveness can also be done through the promotion of entrepreneurship by utilizing local potential and business development services (Wiyadi, 2009).…”
Section: Condition Factormentioning
confidence: 99%
“…Improvement aims to improve the quality of the product, reduce ineffective time and costs, and eliminate some useless activities and improve marketing. Wiyadi (2009) revealed that the conditions of the business environment, each industry must be efficient to be able to compete with domestic products. This is how the industry must be able to offer good quality products at low prices to consumers.…”
Section: Article Infomentioning
confidence: 99%